2013
DOI: 10.2298/gensr1303907d
|View full text |Cite
|
Sign up to set email alerts
|

Variability of factors that affect availability of iron, manganese and zinc in maize lines

Abstract: Deficiencies of some mineral elements are causing serious health problems, which could be prevented by increase of mineral nutrients in food with supplementation, food fortification or plant breeding. From this point, experiment with 78 maize inbred lines was set up to determine maize lines with improved contents of Fe, Zn and Mn, as well as their relations with phytic acid, inorganic phosphorus and ?-carotene, as factors which affect their absorption. Obtained results suggest that investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Otherwise, phytic acid content related negatively with all the studied plant traits. Results align with the studies of Gregorio (2002), Cakmak et al (2010), andDragicevic et al (2013). Chukwudi et al (2022) andGovindaraj et al (2022) reported a positive association between Fe and Zn content; however, they found a negative correlation among Fe-Zn and yield-related traits in maize (Akinwale and Adewopo, 2016;Guo et al, 2020;Bojtor et al, 2021).…”
Section: Correlation Studies Of Plant Traits For Screening Of Maize G...supporting
confidence: 85%
“…Otherwise, phytic acid content related negatively with all the studied plant traits. Results align with the studies of Gregorio (2002), Cakmak et al (2010), andDragicevic et al (2013). Chukwudi et al (2022) andGovindaraj et al (2022) reported a positive association between Fe and Zn content; however, they found a negative correlation among Fe-Zn and yield-related traits in maize (Akinwale and Adewopo, 2016;Guo et al, 2020;Bojtor et al, 2021).…”
Section: Correlation Studies Of Plant Traits For Screening Of Maize G...supporting
confidence: 85%
“…Variations in the ratios between phytate, β-carotene and the mineral nutrients could indicate possible bio-availability of the mineral nutrients (Walter Lopez et al, 2002;Dragičević et al, 2013), with increased tendency of availability with decreasing ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Variations in ratio between phytate (Phy) and β-carotene may indicate possible availability of nutrients [12,23]. This trait is an important parameter for the characterisation of the investigated genotypes.…”
Section: Availability Of Mineral Nutrientsmentioning
confidence: 99%